Dynamics of institutional arrangements for small-scale vegetable farmers in Namibia: An analysis of the market, state and community institutions - Thomas, Benisiu (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.